Protecting the stars of tomorrow: do international cardiovascular preparticipation screening policies account for the paediatric athlete? A systematic review and quality appraisal - Riding, N. R.; Dorobantu, D.-M.; Williams, C. A.; Stuart, G.; Fritsch, P.; Wilson, M. G.; Mossialos, E.; Pieles, G. (British Journal of Sports Medicine, 2023)
Objective: (1) Identify and review current policies for the cardiovascular screening of athletes to assess their applicability to the paediatric population and (2) evaluate the quality of these policy documents using the Appraisal of Guidelines for Research & Evaluation II (AGREE II) tool.